2019
DOI: 10.1139/cgj-2018-0105
|View full text |Cite
|
Sign up to set email alerts
|

Modelling desiccation crack geometry evolution in clayey soils by analytical and numerical approaches

Abstract: In the present work, the development and geometry of desiccation cracks are studied by using a finite element code including cohesive joints elements. The numerical results show that cracking occurs sequentially to form different crack families. The propagation of each crack at the onset suddenly reaches an ultimate depth. The cracks in each family appear simultaneously and reach an identical ultimate depth. From the numerical results and additional analytical analysis, empirical correlations are proposed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This simplifies the problem and allows studying only one half of a periodic cell containing a crack. In reality, the cracking pattern evolves to form sequentially different families of cracks . First, primary cracks are developed dividing the soil surface into cells, and then subsequent drying tends to subdivide these cells in the form of secondary and tertiary crack families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This simplifies the problem and allows studying only one half of a periodic cell containing a crack. In reality, the cracking pattern evolves to form sequentially different families of cracks . First, primary cracks are developed dividing the soil surface into cells, and then subsequent drying tends to subdivide these cells in the form of secondary and tertiary crack families.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, the cracking pattern evolves to form sequentially different families of cracks. 8,75 First, primary cracks are developed dividing the soil surface into cells, and then subsequent drying tends to subdivide these cells in the form of secondary and tertiary crack families. In addition, the crack patterns observed experimentally by Peron et al 34 showed that the crack network formation can result from the combination of two processes, "sequential infilling" and "simultaneous growing," since the cracks tend to appear either successively or simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing attention has been given to the problem of cracks in geotechnical and geological engineering (Baer et al, 2009;Shin and Santamarina, 2011;Hirobe and Oguni, 2016;Tollenaar et al, 2017;Vo et al, 2017;Wang et al, 2017;Pouya et al, 2018;Tang et al, 2018;Vo et al, 2018;Wang et al, 2018;Li et al, 2019;Ruan et al, 2021). Obtaining the geometrical parameters of the primary crack after development, especially the depth, can be used to control engineering disasters in a more accurate, efficient and economical way.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling could capture the essence of desiccation in terms of residual soil height, the number of cracks formed, crack initiation moisture content, and the widths of cracks. Vo et al [15] used finite element code, including cohesive joints, for investigating crack initiation and propagation along with the formation of the crack family. Numerical modelling, though tending to simulate physical processes more accurately, comes in the cost of time and complexity.…”
Section: Introductionmentioning
confidence: 99%